Novel somatic mutations in the BRCA1 gene in sporadic breast tumors - Janatová, Markéta; Zikán, Michal; Dundr, Pavel; Matouš, Bohuslav; Pohlreich, Petr (Human mutation, 2005)
Germline mutations in two major susceptibility genes BRCA1 and BRCA2 contribute to the majority of inherited breast and ovarian cancers. Besides the germline mutation, tumor progression depends on the loss of a wild-type allele. Allelic losses in the BRCA1 and BRCA2 loci have also been detected in a high proportion of sporadic breast tumors, suggesting the role of these genes in the development of non-inherited breast cancer. Forty unselected breast tumors were analyzed for the loss of heterozygosity (LOH) at BRCA1 and BRCA2 regions and tumors with allelic deletions were screened for the presence of acquired genetic alterations in respective genes. 21.1% of 38 informative tumor samples carried LOH at the BRCA1 locus whereas 33.3% of 39 informative samples showed LOH at the BRCA2 locus. Pathogenic truncating mutations in the BRCA1 gene were found in two tumor samples with allelic losses, whereas no mutations were identified in the BRCA2 gene. Mutations were not detected in non-tumor samples from the same individuals, which indicated that the BRCA1 allele was inactivated by somatic mutations in tumor tissue. The c.1116G>A (1235G>A) nonsense mutation (p.W372X) belongs to the genetic abnormalities detected infrequently in hereditary tumors; the c.3862delG (3981delG) frameshift mutation (p.E1288fsX1306) is a novel gene alteration. The occurrence of inactivating somatic mutations in sporadic breast tumors suggested the role of the BRCA1 gene in tumorigenesis in at least a minor group of patients with non-familial breast cancer. (c) 2005 Wiley-Liss, Inc.
Keywords: posun čtecího rámce na ribozómech; duktální karcinom prsu; Humans; lidé; lidé středního věku; Middle Aged; geny BRCA2; Female; nesmyslný kodon; Adult; DNA Mutational Analysis; Frameshifting, Ribosomal; Breast Neoplasms; BRCA1 Protein; Genes, BRCA1; mutační analýza DNA; Carcinoma, Ductal, Breast; geny BRCA1; ženské pohlaví; Codon, Nonsense; Microsatellite Repeats; nádorová transformace buněk; DNA, Neoplasm; Genes, BRCA2; nádory prsu; dospělí; DNA nádorová; mikrosatelitní repetice; Loss of Heterozygosity; ztráta heterozygozity; protein BRCA1; Cell Transformation, Neoplastic